One-Shot Dual-Code Immunotargeting for Ultra-Sensitive Tumor Necrosis Factor‑α Nanosensors by 3D Enhanced Dark-Field Super-Resolution Microscopy - Ju, Soyeong; Lee, Seungah; Chakkarapani, Suresh Kumar; Kim, Kyungsoo; Yu, Hyunung; Kang, Seong Ho (Analytical chemistry (Washington), 2018)
Tumor necrosis factor-α (TNF-α) is a significant mediator of autoimmune diseases and an inflammatory protein biomarker. A novel method for the immunotargeting of TNF-α has been developed using three-dimensional (3D) enhanced dark-field super-resolution microscopy (3D EDF-SRM) based on ultrasensitive dual-code plasmonic nanosensing. Dual-code EDF-based 3D SRM improved the localization precision and sensitivity with a least-cubic algorithm, which provides accurate position information for the immunotargeted site. A dual-view device and digital single-lens reflex (DSLR) camera were used for simultaneous dual confirmable quantitative and qualitative immunoscreening based on enhanced dark-field scattering images. Two different sizes of silver nanoparticles (40- and 80-nm AgNPs) were compared to enhance the scattering signal of the immunotargeted plasmonic nanoprobe for the 3D EDF-SRM system. The standard TNF-α was immunotargeted at a single-molecule level and was quantitatively analyzed by measuring the scattering signals of 80 nm AgNPs on an array chip with gold-nanostages (GNSs) with 100 nm spot diameters. The localization precision in the 80 nm AgNP immunotag on the GNS narrowed to ∼9.5 nm after applying the least-cubic algorithm. The developed nanosensor exhibited a detection limit of 65 zM (1.14 ag/mL; S/N = 3) with a wide dynamic detection range of 65 zM–2.08 pM (1.14 ag/mL–36.4 pg/mL; R = 0.9921). These values are 20–33 400 000 times lower than detection limits obtained using previous methods. In addition, a recovery greater than 98% was achieved by spiking standard TNF-α into human serum samples. This method should facilitate simultaneous improvements in immunotargeting precision and ultrahigh sensitive detection of various disease-related target protein molecules at a single-molecule level.